Topological interlocking in architecture: A new design method and computational tool for designing building floors. (June 2017) - Weizmann, Michael; Amir, Oded; Grobman, Yasha Jacob
This article presents a framework for the design process of structural systems based on the notion of topological interlocking. A new design method and a computational tool for generating valid architectural topological interlocking geometries are discussed. In the heart of the method are an algorithm for automatically generating valid two-dimensional patterns and a set of procedures for creating several types of volumetric blocks based on the two-dimensional patterns. Additionally, the computational tool can convert custom sets of closed planar curves into structural elements based on the topological interlocking principle. The method is examined in a case study of a building floor. The article concludes with discussions on the potential advantages of using the method for architectural design, as well as on challenging aspects of further development of this method toward implementation in practice.